The fear of goods from Hesiod to Adam Smith - Perrotta, Cosimo, 1942-; ProQuest (Firm) (London ; New York : Routledge, 2004)
This work explores the changing place of consumption as a source of investment in production and growth within economic writings from ancient history to the present. This project is carried out with great skill, vigour and originality and will help to bring consumption studies to the mainstream of economic thought.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Consumption (Economics); Production (Economic theory); Electronic books